تأثير التطورات في بيئة الاعمال على المحاسبة الادارية في القرن الحادي والعشرين - د. قاسم محسن الحبيطي; زياد هاشم يحيى (PROSPECTIVE RESEARCHES, 2023)
The present research aims at introducing the predicted developments in the 21st century the business environment. It also tackles the effect of these developments on the management accounting and the required role played by management accountants to satisfy their duties towards the organization they work at to be familiar with the great rapid developments. Therefore, the following issues can be identified like: The reasons led to the appearance of management accounting in the last century, The main predicted appearances in the present century and their effect on the management accounting, and The required role from the management accounting to satisfy their duties under the developments and changes predicted in the 21st century.